1981
DOI: 10.1002/j.1556-6978.1981.tb01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Baccalaureate Programs in Counseling: Follow‐up and Implications

Abstract: Several counselor education programs across the country have become increasingly involved in the training of helping professionals at the undergraduate level. This article reports the results of a follow‐up study of the first 144 graduates of the baccalaureate programs offered in the department of Counseling and Personnel Services at the University of Missouri‐Columbia. The author also describes what the graduates did initially on completion of their programs and suggests several implications that baccalaureat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Few follow-up studies of counseling graduates or systematic studies of entry level employment patterns or needs have been published. Those published have tended to relate to new or special interest areas such as women in college student personnel work (Kuh, 1979) or undergraduate guidance majors Schmitz, 1981). No previous followup studies of counseling graduates with gerontological training have been found in national journals.…”
mentioning
confidence: 99%
“…Few follow-up studies of counseling graduates or systematic studies of entry level employment patterns or needs have been published. Those published have tended to relate to new or special interest areas such as women in college student personnel work (Kuh, 1979) or undergraduate guidance majors Schmitz, 1981). No previous followup studies of counseling graduates with gerontological training have been found in national journals.…”
mentioning
confidence: 99%